Anxiety and coping strategies of judo competitors (Revista de Artes Marciales Asiáticas, 2018)
The aim of this study was to describe the anxiety responses and coping strategies used by competitive judokas of different sex category, level of performance, experience and age category. The sample was composed of 58 competitive Spanish judokas. They completed a battery of test composed by a socio-demographic questionnaire, the CSAI-2R and the ISRA-B, responses version, to evaluate anxiety. Finally, we used the ISCCS to evaluate the judokas’ coping strategies. The results showed that women, low performance judokas, experienced judokas and the top age categories (junior and senior) presented high levels of anxiety and lower auto confidence. Correlational analysis showed that judokas’ most used strategies were task oriented coping (TOC), though with high levels of anxiety they choose emotional oriented coping (EOC), which the scientific literature does not associate with good performance. In addition, high levels of auto confidence correlated positively with distraction-oriented coping (DOC). The practical implication of this work relates to the usefulness of this information for the improvement and optimization of competitive judokas’ copying strategies.